Geoprocessamento: estudos de Geomarketing e as possibilidades de sua aplicação no planejamento do desenvolvimento socioeconômico - Furlan, Adriana Aparecida (GEOUSP Espaço e Tempo (Online), 2011)
The advances in knowledge of the land surface and the large amount of data that can be inserted in the maps led to the development and use of specific software focused on the development of a computerized mapping supported by the use of computers. Thus the Geographic Information System enables the handling of large volumes of data and making analysis more complex. This gave rise to various possibilities of analysis of reality and also resulted in its application to various fields of knowledge. One of these areas of application of computerized cartography is known as Geomarketing. Based on theories of urban geography, to understand the urban space, and market knowledge, the Geomarketing has been used by public and private companies in planning and socioeconomic development in countries like Brazil, on a larger scale, and Mozambique, still in expansion phase.